2007
DOI: 10.1211/jpp.59.11.0002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of human pharmacokinetics — renal metabolic and excretion clearance

Abstract: The kidneys have the capability to both excrete and metabolise drugs. An understanding of mechanisms that determine these processes is required for the prediction of pharmacokinetics, exposures, doses and interactions of candidate drugs. This is particularly important for compounds predicted to have low or negligible non-renal clearance (CL). Clinically significant interactions in drug transport occur mostly in the kidneys. The main objective was to evaluate methods for prediction of excretion and metabolic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 58 publications
0
52
0
1
Order By: Relevance
“…Benet et al (2011) reported that percent of unchanged drug excreted into urine was statistically lower for compounds belonging to classes 1 and 2 than for compounds belonging to classes 3 and 4. Although, a low CL R is not necessarily due to net reabsorption, lipophilicity of compounds is a significant determinant of extensive metabolism and distribution of compounds (Fagerholm, 2007). As well, compounds that undergo extensive metabolism are less likely to undergo biliary and renal excretion (Fagerholm, 2007;Benet et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Benet et al (2011) reported that percent of unchanged drug excreted into urine was statistically lower for compounds belonging to classes 1 and 2 than for compounds belonging to classes 3 and 4. Although, a low CL R is not necessarily due to net reabsorption, lipophilicity of compounds is a significant determinant of extensive metabolism and distribution of compounds (Fagerholm, 2007). As well, compounds that undergo extensive metabolism are less likely to undergo biliary and renal excretion (Fagerholm, 2007;Benet et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although, a low CL R is not necessarily due to net reabsorption, lipophilicity of compounds is a significant determinant of extensive metabolism and distribution of compounds (Fagerholm, 2007). As well, compounds that undergo extensive metabolism are less likely to undergo biliary and renal excretion (Fagerholm, 2007;Benet et al, 2011). Moreover, compounds undergoing net reabsorption were predominantly neutral.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These model input parameters are derived either from in silico predictions based on the chemical structure (logP, pK a , polar surface area), from in vitro experiments designed to mimic certain bodily environments, or from in vivo measurements. In 2007, Fagerholm evaluated the various methods available for the scaling of in vitro measurements for the prediction of hepatic metabolic clearance [37], renal clearance [38], intestinal metabolism [39] and absorption [40], and volume of Figure 2. Structure of the gut model [28].…”
Section: Pbpk Model Structure and Parameterizationmentioning
confidence: 99%